THE EVALUATION OF NATIONAL QUALIFICATION FRAMEWORK CURRICULUM (KKNI) AT UIN RADEN FATAH PALEMBANG - Fitri Oviyanti; Indrawati Indrawati; Siti Rochmiatun; Arne Huzaimah; Zuhdiyah Zuhdiyah; Alfurqan Alfurqan (Ta'dib, 2020)
Abstract: The purpose of the research was to evaluate the implementation of KKNI based curriculum.  This study was a case study within qualitative approach. The data collection techniques were interviews, observation, and documentation. The data were analysed by using Miles and Huberman techniques. From the result of data analysis it was found that 1). in the aspect of the context variable, the perception of lecturers and students about curriculum implementation based on KKNI was already good, but the perceptions of the educational staffs were not good, 2). in terms of the input variable, it was seen from three points; the vision and mission, KKNI socialization, and learning management. Vision and Mission of UIN supports KKNI, socialization of KKNI is very intense at UIN Raden Fatah, good management supports the socialization of KKNI 3). from the aspect of the process variable, in the learning process, the lecturers of Faculty of Tarbiyah and Teacher Training (FITK) tended to have implemented student-centered learning. Meanwhile the lecturers of Faculty of Sharia and Law (FSH) still tended to implement teacher- centered learning processes, and 4). in terms of product variable, the students’ achievement was very good. Abstrak: Tujuan penelitian ini adalah untuk mengevaluasi pelaksanaan kurikulum berbasis KKNI. Penelitian ini merupakan studi kasus dengan pendekatan kualitatif. Teknik pengumpulan data adalah wawancara, observasi, dan dokumentasi. Analisis data menggunakan teknik Miles dan Huberman. Dari hasil analisis data ditemukan bahwa 1). Pada aspek variabel konteks, persepsi dosen dan mahasiswa tentang penerapan kurikulum berbasis KKNI sudah baik, namun tenaga kependidikan kurang baik, 2). dari segi variabel masukan dilihat dari tiga hal yaitu; visi dan misi, sosialisasi KKNI, dan manajemen pembelajaran. Visi dan Misi UIN mendukung KKNI, sosialisasi KKNI sangat intens di UIN Raden Fatah, manajemen yang baik mendukung sosialisasi KKNI 3). Dari aspek variabel proses, dalam proses pembelajaran dosen Fakultas Tarbiyah dan Keguruan (FITK) cenderung menerapkan pembelajaran yang berpusat pada siswa. Sedangkan dosen Fakultas Syariah dan Hukum (FSH) masih cenderung menerapkan proses pembelajaran yang berpusat pada guru, dan 4). Dilihat dari variabel produk, prestasi belajar siswa sangat baik.